Synergistic doping of Iron and selenium on nickel hydroxide nitrate nanoarrays-derived as an efficient electrocatalyst for overall water splitting - Le, Huu Tuan; Chun, Hee Joon; Kwon, Yong Jung; Ham, Min Ji; Kim, Seok Ki; Jeong, Young Kyu (Applied Surface Science, 2024)
The fabrication of highly efficient and stable catalysts for water oxidation is important to promote the development of the hydrogen fuel industry. In this study, dual-element-doped two-dimensional nickel hydroxide nitrate nanoarrays (NiHN) self-supported on nickel foam were fabricated via a facile electrodeposition process. The results demonstrated that Fe and Se were incorporated into the nickel hydroxide structure. The binder-free FeSe-NiHN catalyst exhibited low overpotentials of 129 and 250 mV at 10 mA cm−2 for the hydrogen evolution reaction and at 100 mA cm−2 for the oxygen evolution reaction in 1 M KOH media, respectively. Furthermore, a durability test conducted at 70 mA cm−2 for 28 h showed no evident degradation of the catalyst activity, verifying its exceptional stability. Thus, FeSe-NiHN is a potential water splitting electrocatalyst for inexpensive hydrogen production.
Keywords: Efficient catalysts; Fuel industries; Iron doping; Nanoarrays; Nickel hydroxide nitrate nanoarray; Nickel hydroxides; Selenia doping; Stable catalysts; Water oxidation; Water splitting; Electrodeposition; Iron doping; Nickel hydroxide nitrate nanoarrays; Selenium doping; Water oxidation